When personality is the problem: Managing patients with difficult personalities on the acute care unit. Issue 12 (9th September 2016) - Riddle, Megan; Meeks, Timothy; Alvarez, Carrol; Dubovsky, Amelia
Abstract : Personality disorders are pervasive patterns of maladaptive behaviors, thoughts, and emotions that often go unrecognized and can wreak havoc in the patient's interpersonal life. These inflexible patterns of managing the world can be disruptive when an individual is admitted to the hospital, causing distress for both the patient who lacks the skills to deal with the expectations of the hospital environment and the treatment team who can feel ill equipped to manage such behavior. Having a personality disorder has implications for an individual's healthcare outcomes; those with a personality disorder have a life expectancy nearly 2 decades shorter than the general population for a multitude of reasons, among them trouble interacting with the healthcare system. Although a diagnosis of a specific personality disorder may be difficult to make on an acute care unit, identification of dysfunctional personality structures can provide opportunity for better management of an individual patient's medical and psychological needs. This review focuses on the identification of these individuals in the acute care setting and provides an overview of evidence‐based behavioral and pharmacological interventions. Journal of Hospital Medicine 2015;11:873–878. © 2015 Society of Hospital Medicine